In the Story "Garden Party" Through Agoronym Analysis of the Image of Society (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The Garden Party is one of Katherine Mansfield's most famous short stories, masterfully exploring themes such as human emotions, social stratification, and the importance of appearance through the simple moments of life. The main character of the story, Laura, is preparing to organize a lavish party with her partners, but in the process, she thinks more deeply about the differences between different layers of society.In the course of the article, through this story, how the author expressed the contradictions between the inner world and external conditions, and how important qualities such as humanity and sincerity are. It also speaks to Mansfield's unique style and skill in detailing the story's relevance for modern readers.